HucMSC-sEVs-Derived 14-3-3ζ Serves as a Bridge between YAP and Autophagy in Diabetic Kidney Disease. (22nd September 2022) - Yin, Siqi; Liu, Wanzhu; Ji, Cheng; Zhu, Yuan; Shan, Yunjie; Zhou, Zixuan; Chen, Wenya; Zhang, Leilei; Sun, Zixuan; Zhou, Wenqin; Qian, Hui
Abstract : As nanoscale membranous vesicles, human umbilical cord mesenchymal stem cell-derived small extracellular vesicles (hucMSC-sEVs) have attracted extensive attention in the field of tissue regeneration. Under the premise that the mechanisms of hucMSC-sEVs on the treatment of diabetic kidney disease (DKD) have not been revealed clearly, we constructed DKD rat model with success. After tail vein injection, hucMSC-sEVs effectively reduced blood glucose, maintained body weight and improved renal function in DKD rats. Notably, we found that hucMSC-sEVs suppressed YAP expression in renal cortical regions. Further in vitro experiments, we confirmed that the expression of YAP in the nucleus of renal podocytes was increased, and the level of autophagy was inhibited in the high-glucose environment, which could be reversed by intervention with hucMSC-sEVs. We screened out the key protein 14-3-3 ζ, which could not only promote YAP cytoplasmic retention instead of entering the nucleus, but also enhance the level of autophagy in the cytoplasm. Ultimately, excessive YAP protein was removed by autophagy, a classic way of protein degradation. In conclusion, our study provides new strategies for the prevention of DKD and proposes the possibility of hucMSC-sEVs becoming a new treatment for DKD in the future.